A resistência da educação no campo em época de pandemia na comunidade quilombola alto Acaraqui no município de Abaetetuba - CARDOSO, Aurilucy de Jesus dos Santos Souza (2024)
The objective of this study is to describe the forms of resistance in rural education, through the quilombola community of Acaraqui in the municipality of Abaetetuba in the midst of the COVID-19 pandemic, in the initial grades at the Municipal School of Child and Elementary Education São Tomé from Alto Acaraqui during the period of social distancing. It is intended to carry out a descriptive, cross-sectional and population-based study with residents of the indicated community in the municipality of Abaetetuba. Educational practices during the pandemic, place of practice and educational and pedagogical guidance were described. The sample is intended to analyze about 10 respondents among students, teachers and school managers.